Study On The Mechanical Properties Of Two Species Of Bamboo (Gigantochloa Ligulata And Gigantochloa Scortechinii) A Systematic Literature Review - Mohamed, Areeg Yasser (Universiti Sains Malaysia, 2021)
This research reviews on the studies that have been done by previous researchers on the anatomical and mechanical properties of bamboo. Bamboo is the best choice for replacing timber because of its high strength and rapid growth. Bamboo grows in a wide range of climates, from the coldest mountains to the hottest tropical regions. Bamboo covers approximately forty million ha of land, mostly in Asia. Nowadays, with the current emphasis on environmental friendliness and sustainability, natural fibre composites are more preferred over conventional fibre which is normally non-biodegradable. Bamboo is a type of natural fibre composites that are widely used in many industries such as in construction. Hence, it is crucial to study the mechanical properties of bamboo to make sure it is safe for certain applications. However, there are many factors that determine the anatomical and mechanical properties of bamboo such as species, age and density, moisture content, etc. This research reviews on some of the research on the mechanical properties of pure bamboo and bamboo composites such as their tensile properties, compressive properties, impact strength and fracture toughness. The research includes how the researchers set up their experiments, the bamboo species used, and the results obtained. Bamboo has no standard building codes in most countries, making it nearly impossible for those who choose to use it in construction. There is some legal ambiguity concerning the determination of certain bamboo properties including fire resistance, strength properties, and longevity implying that regulations and standards are urgently needed. Bamboo’s strength properties have already been checked, and the findings are excellent, in many cases of traditional building materials. However, building code regulations need more than a material's strength properties; other properties to consider include durability, fire safety, environmental impact, usability, and energy efficiency.